1999
DOI: 10.1046/j.1365-2788.1999.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Health screening for people with intellectual disability: the New Zealand experience

Abstract: People with intellectual disability have considerable health needs and variable health care. The introduction of annual health screens for IHC residents in New Zealand resulted in some 73% of screened people requiring follow-up interventions. The introduction of the health screens raised a number of issues for management, staff, health professionals and clients who might subsequently be involved in an exercise of this type and magnitude. The importance of applying principles of management promoted by proponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 15 publications
(10 reference statements)
6
78
0
1
Order By: Relevance
“…This supports the finding of the previous review that studies consistently provide evidence of health checks leading to targeted actions to address identified health needs (Baxter et al, 2006;Bollard, 1999;Hunt et al, 2001Hunt et al, , 2006Lennox et al, 2006Lennox et al, , 2007Lennox et al, , 2008Lennox et al, , 2010Lennox et al, , 2011Martin, Axon, et al, 2004;Martin, Philip, et al, 2004;McConkey et al, 2002;Webb & Rogers, 1999). In the UK, an audit of actions resulting from health checks for 190 participants, of whom 93 had new health needs identified, indicated that management had been initiated for 90% of identified needs by the time of the audit and treatment concluded for 61% of needs (Baxter et al, 2006).…”
Section: Health Actions Resulting From Health Checkssupporting
confidence: 85%
See 2 more Smart Citations
“…This supports the finding of the previous review that studies consistently provide evidence of health checks leading to targeted actions to address identified health needs (Baxter et al, 2006;Bollard, 1999;Hunt et al, 2001Hunt et al, , 2006Lennox et al, 2006Lennox et al, , 2007Lennox et al, , 2008Lennox et al, , 2010Lennox et al, , 2011Martin, Axon, et al, 2004;Martin, Philip, et al, 2004;McConkey et al, 2002;Webb & Rogers, 1999). In the UK, an audit of actions resulting from health checks for 190 participants, of whom 93 had new health needs identified, indicated that management had been initiated for 90% of identified needs by the time of the audit and treatment concluded for 61% of needs (Baxter et al, 2006).…”
Section: Health Actions Resulting From Health Checkssupporting
confidence: 85%
“…Other common actions included: immunisations (Hunt et al, 2001;Lennox et al, 2006Lennox et al, , 2007Lennox et al, , 2008Lennox et al, , 2010; screening for breast, testicular or cervical cancer (Hunt et Martin, Philip, et al, 2004;McConkey et al, 2002); and general health promotion such as healthy eating advice (Hunt et al, 2006). In addition to these what might be considered routine actions, a number of life saving actions have been noted including: provision of a pacemaker, surgery for previously undetected melanoma, and mastectomy for previously undetected breast cancer (Webb & Rogers, 1999); and surgery and radiotherapy for seminoma (Wilson & Haire, 1990).…”
Section: Health Actions Resulting From Health Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…The research indicates that people with learning disabilities have greater healthcare needs than the general population with many of these needs remaining unmet (Van Schrojenstein Lantman-de Valk et al 1997, Center et al 1998, Scott et al 1998, Barr et al 1999, Bohmer et al 1999, Webb & Rodgers 1999, Hunt et al 2001, Cassidy et al 2002. In addition, the efforts to address these healthcare deficits continue to pose significant challenges to healthcare services, with many professionals within mainstream health services having a little or no education about intellectual disability (NHS Executive 1999, Horwitz et al 2000, DoH 2001, NHS Scotland 2002, DHSSPS 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Current literature suggests that 'health assessments' or 'health checks' may increase the number of health actions, case-finding activity, and disease identification and management in people with ID (Robertson et al, 2014). Health assessments have been seen to increase diagnoses, including diagnosis of thyroid disorders, diabetes, hypertension, and then result in positive healthcare activity, for example, the provision of a pacemaker and surgery for previously undetected melanoma (Robertson et al, 2014;Webb & Rogers, 1999). Preliminary literature does indicate that health assessments may increase the number of health actions, in which case they may reduce unmet health needs and improve healthcare, contributing positively to longer-term health outcomes.…”
Section: Chapter Twomentioning
confidence: 99%